Impact Assessment from Enacting Cap-and-Trade Legislation in Thailand's Industrial Estates - Varoon Raksakulkarn; Chaichan Ritkrerkkrai; Wongkot Wongsapai; Piangsakul Yodchumpoo; Sopit Daroon; Waranya Thepsaskul; Phitsinee Muangjai (Chemical Engineering Transactions)
Industrial estates are designated areas of land allocated for industrial factories to operate together in proportion, resulting in significant energy consumption and greenhouse gas (GHG) emissions in Thailand. Presently, there are 61 operational industrial estates, dispersed across 17 provinces. These estates accommodate over 1,295 designated factories, which extensively utilize energy resources and emit considerable quantities of GHG annually. Cap-and-trade is one of the carbon pricing mechanisms widely employed across numerous countries. It stands as an effective policy instrument aimed at reducing GHG emissions through legislative mandates that enforce major emitters to decrease their GHG emissions. This study evaluated GHG emissions from energy consumption in designated factories within industrial estates. It assessed the potential applicability of cap-and-trade mechanisms based on the European Union Emissions Trading System (EU ETS) thresholds and other assumptions for different scenarios. Additionally, it estimated the factory's administrative burdens resulting from legislative mandates, employing the Standard Cost Model (SCM). The study identified the number of designated factories emitting GHG beyond the set threshold between 45 and 200. Their combined emissions amounted to 9.20–43.34 MtCO2e/y. Moreover, the study revealed that factories incurred a time-related compliance cost of 4,365–19,400 h/y and a financial compliance cost of 8–36 million Baht per year. Findings can be utilized for subsequent regulatory impact assessment (RIA).